Three-dimensional phase field simulation for rafting of multiparticle precipitate in elastic inhomogeneous alloy under external stress - Mao H.; Kong Y.; Shuai X.; Tang S.; Du Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Nickel-based super alloys are the main candidate materials for aero-engines, gas turbine blades etc. This paper focuses on the simulation of nucleation and growth kinetics of γ' phase, and stress response mechanism of γ’ phase particles during their preferential coarsening (rafting) in elastic inhomogeneous system. A phase-field model is employed in the present study, which incorporates chemical, interfacial, and elastic energies, and it couples essentially to externally imposed mechanical field. Due to the limitations of the 2D model on analyzing the shape and size of the precipitate particles, the process of γ' phase particles growing and coarsening is further modeled by performing 3D simulation. The results show that the average particle size is linearly related to the evolution time and satisfies the Lifshitz-Slyozov-Wagner (LSW) classical coarsening theory when the external stress is not applied. Particles exhibit a strong special orientation under tensile stress, and the orientation is in excellent agreement with previous studies. In the nucleation stage, the collision and coalescence between particles promote rafting significantly, and the number of soft particles is obviously larger than that of hard particles. In the coarsening stage, the growth rate of soft particles is higher than that of hard particles. Three-dimensional simulation results show that the effect of final characteristic size of precipitated particles is not significant by external loads. The morphology evolution and coarsening mechanism of the precipitated particles are of great significance for studying the strengthening mechanism of super-alloy.